INFLUENCE OF TEMPERATURE AND GLUCOSE ON PRODUCTION OF THERMO STABLE ENTEROTOXIN OF YERSINIA ENTEROCOLITICA - MM; Soltan Dallal (Tehran University of Medical Sciences, 2000)
Yersinia enterocolitica is newly included in the classification of both the invasive bacteria, e.g. Shigella, and the toxicogenic bacteria, e.g. Escherichia coli. Five human strains and 45 environmental strains were used to produce Y.enterocolitical enterotoxin at 40C, 240C and 370C using infant mouse assay. At 250C enterotoxin was produced by 10 environmental strains and by all of the 3 human strains. At 40C, enterotoxin was produced by only 3 environmental strains. At 370C, none of the strains produced enterotoxin. This enterotoxin was stable for 60 min at 1000C and 1210C (autoclave) for 20 min and did not lose its activity in infect mouse assay. Increased production on enterotoxin was observed following addition of 0.4% glucose in culture medium only at 250C, but not at 370C.